23 outstanding students from the Faculty of Business and Management achieve prestigious EUMMAS certification - UiTM, Faculty of Business and Management (UiTM, 2023)
Twenty-three outstanding students from the Faculty of Business and Management (FBM) successfully obtained the prestigious EUMMAS Certification, demonstrating their commitment to academic excellence and professional competency. This achievement reflects the faculty’s continuous efforts in enhancing students’ employability, industry-relevant skills, and global recognition through internationally acknowledged professional certifications.